The Role of Intellectual Capital in Developing the Competitive Tishreen University abilities - مرهج ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed at determining the role of intellectual capital in developing the competitive Tishreen University Abilities in both education and scientific research. The researcher relied on the methodological approach as a general approach to research, followed the methodology of the survey, and a set of methods, including relying on secondary and primary data through a questionnaire that was organized by the researcher’s knowledge of published literature. He distributed the questionnaire to 331 members of the faculty of Tishreen University, 263 of which were recovered, and 13 were not valid for analysis in the research community comprised of staff in Tishreen University faculty, of the 2376 respondents according to statistics of the Directorate of Statistics and Planning, and then used the appropriate statistical tests, such as simple regression, and rely on a programme SPSS is applying to be a tool for analysis of Data available. The main conclusion was a moral role, an Acceptable correlation between intellectual capital and competitive ability. Some suggestions and recommendations were presented to improve the relationship, which is the most important: the need to work for improvement of the level of education and scientific research in order to achieve the university’s competitive ability.